Introduction of China’s Copper Converting Technologies - Feng He; Huilan Yang (Canadian Institute of Mining, Metallurgy and Petroleum, 2019)
This paper intends to introduce the development of copper smelting and converting technologies in China in recent years, with a particular emphasis on the introduction of various continuous converting technologies, and moreover, it analyzes the advantages and disadvantages of those technologies, including their impact on the downstream anode refining from different points of view. INTRODUCTION At present, many converting technologies are used in copper pyro-metallurgical plants in China, including Peirce-Smith (PS) converter, flash converting furnace, multi-lance based top blowing, bottom blowing and so on. These technologies have spanned a wide range of time. PS converter technology has been applied in copper smelters for many years and most of the blister copper have been produced by this technology; flash converting technology has been developed since 1990s and been maturely applied in several plants up until now; top blowing and bottom blowing technologies have been revived in China in the past decade and boast good environmental protection performance, energy efficiency, throughput capacity and short process flow. All of the said technologies have reference operations in treating high-grade matte. As more and more attention is paid to environmental protection globally and copper smelters continuously seek for cost reduction, it is necessary to share those converting technologies, especially those new converting technologies derived in China, with copper smelting practitioners in the world. This paper aims to analyze the advantages and disadvantages of various technologies from a macroscopic view and discuss their actual application effects, current developments and future improvements. BRIEF INTRODUCTION OF VARIOUS CONVERTING TECHNOLOGIES IN CHINA China has seen a rapid development in copper smelting industry in the past 30 years and has become the largest gathering place of copper smelters in the world, most of which are operating with PS converting furnace technology, however, with the increasingly strict environmental requirements of the Chinese government in recent years, the low-level pollution issue and the disadvantage of large gas exhaust amount per unit of copper of converting furnaces are particularly prominent.